R and L in the warsh transmission (compared to the hafs transmission) - Garadaghly, Vugar A. (Technium Social Sciences Journal, 2021)
In the research, pronunciation features of r and l consonants were studied on the basis of Hafs and Warsh transmission systems narrated from Asim and Nafe, respectively, where different characteristics of the mentioned consonants were investigated both within the two transmission systems and in comparison to each other, by means of an applied comparative method. Additionally, it was noted that conclusions derived from studied Hafs transmission system narrated from Asim were topical also for the modern Arabic language. Conducted statistical analysis and a comparative study of the two transmission systems enable us to define the linguistics norms of r and l consonants for both transmission systems. It is noted that in the transmission system narrated from Asim there is no norm for r consonant, that is to say, there is no stable norm for r sound in the accommodation system, as it is characterized as two different sounds, being pronounced both as a hard sound and as a soft sound in definite situations, which is related to the influence of sounds around it, making the two cases as two different norms. Differently from the Hafs transmission system, in the Warsh transmission system, in case of an adjoining or short [a] sound with interval emphatic [s], [t] or [z] sound, an open and short or a long vowel before l or double l sound with a following non-labialized, open and short or long sound, it is pronounced, within the emphatic feature, as a hard sound with incomplete onward adjoining or interval adaptation.